2020
DOI: 10.1002/ldr.3636
|View full text |Cite
|
Sign up to set email alerts
|

Are annual nitrous oxide fluxes sensitive to warming and increasing precipitation in the Gurbantunggut Desert?

Abstract: Temperate desert soils are an important source of atmospheric nitrous oxide (N2O). However, it is uncertain how N2O emissions respond to warming, increased rainfall and nitrogen (N) addition in such soils. A multifactorial field manipulation study was carried out in the Gurbantunggut Desert, China's second largest desert, to investigate how these factors influence desert soil N2O emissions and to assess inter‐year variation. In our 3‐year study, under current climatic conditions, the annual flux of N2O in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
4
7
2
Order By: Relevance
“…This can be attributed to the following factors: The precipitation change did not significantly change the abundance of key functional microorganisms in the nitrification and denitrification processes (Figure 1), and increasing the precipitation during this period of precipitation concentration enhanced the soil's anaerobic environment, increased the total denitrification rate, and promoted the generation of N 2 O to be converted into nitrogen; accordingly, no significant changes occurred in the N 2 O emissions (Barnard et al, 2005). In addition, the precipitation changes had no significant effect on N 2 O emissions in the nongrowing season (Figures 2 and 3), which is consistent with the results of previous research (Yue, Cui, et al, 2021). This is attributed mainly to the limitations of insufficient precipitation and excessively low soil temperature in the nongrowing season (Figure 2a).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This can be attributed to the following factors: The precipitation change did not significantly change the abundance of key functional microorganisms in the nitrification and denitrification processes (Figure 1), and increasing the precipitation during this period of precipitation concentration enhanced the soil's anaerobic environment, increased the total denitrification rate, and promoted the generation of N 2 O to be converted into nitrogen; accordingly, no significant changes occurred in the N 2 O emissions (Barnard et al, 2005). In addition, the precipitation changes had no significant effect on N 2 O emissions in the nongrowing season (Figures 2 and 3), which is consistent with the results of previous research (Yue, Cui, et al, 2021). This is attributed mainly to the limitations of insufficient precipitation and excessively low soil temperature in the nongrowing season (Figure 2a).…”
Section: Discussionsupporting
confidence: 91%
“…The results of the 2‐year study showed that N 2 O emission is relatively low in the desert steppe, at −0.04 to +15.0 μg N m −2 hr −1 (Figure 2). Although this range is consistent with that reported previously for grassland, desert, and north Australian savanna soils (W. W. Chen et al, 2013; Grover et al, 2012; Yue, Cui, et al, 2021), it is significantly lower than that of agricultural soil (C. Liu et al, 2012). An interesting result of the present study is that N 2 O was occasionally absorbed by the soil, particularly when the precipitation was reduced 60% (Figure 2).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations